Sumber Daya Budaya Pendukung Perkembangan Kota Pengalaman Santa Fe mengubah kekayaan budaya local menjadi sumberdaya pertumbuhan ekonomi wilayah - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Pascasarjana Universitas Gadjah Mada, 2000)
Cultural assets were rarely recognized and therefore accounted for as resources for local development. A modified city management framework was proven to be effective means to "convert" Santa Fe's historic and cultural heritage into resources for its economic growth. Management framework was utilized and further accompanied by detailed inventories and spatial delineations to ensure appropriate development control.